Metodologia para geração de seção de choque - Patricia Alves Franca de Mesquita (2015)
Due to the complexity of a nuclear reactor and a constant need of to have accurate and reliable data, specific nuclide temperatures have become necessary in simulations. The rise in temperature results in resonance peaks expansion and reduction of cross section values, thus decreasing the probability of neutrons interactions. The MCNPX code has been used widely for simulation of nuclear systems. However, for most isotopes, the standard nuclear data have been generated at room temperature. Therefore, the goal of this study is to develop a methodology for generating a nuclear data library to be used in MCNPX 2.6.0. In this context, the code NJOY99 is used for processing nuclear cross section data for different temperatures. The data is then added to the MCNPX 2.6.0. pre-defined library set. This study has great importance to understand and analyze the critical differences estimated by MCNPX due to different reactor operation temperatures. The first results of this study are presented and evaluated as well as they point out the necessity for further research on this topic